THE EFFECT OF PROFITABILITY, LEVERAGE, AND LIQUIDITY ON TAX AVOIDANCE - Helen; Haninun (ZILLZELL MEDIA PRIMA, 2024)
Tax avoidance is a business practice that uses accounting techniques that comply with tax rules by exploiting legal loopholes to reduce their total tax liability. The purpose of this study is to gather empirical evidence on the relationship between tax avoidance and accounting profitability, leverage, and liquidity. Using a sample of banking organizations registered in the IDX for the years 2018-2022, the study was carried out statistically. A linear multiple analysis is utilized in the analytical method. Partial research findings show that profitability factors affect while leverage and liquidity have no effect on tax avoidance, but simultaneously profitability, leverage, and liquidity affect tax avoidance.